Upaya Meningkatkan Hasil Belajar Dribbling Sepak Bola Dengan Menggunakan Metode Pembelajaran Resiprokal: Kristina Merry Silla, Rajidin, Henry Maksum (Journal Sport Academy, 2024)
The purpose of this study was to determine the improvement of soccer dribbling learning outcomes using the reciprocal teaching method for Grade XI IIS students at Sekolah Menengah Atas Negeri 1 Sekadau, Sekadau Regency. The method employed in this research was Classroom Action Research with a descriptive approach. The data collection techniques used were direct observation and measurement, while the instruments included observation guidelines and measurement tests. The subjects of this study were 36 students of Grade XI IIS at Sekolah Menengah Atas Negeri 1 Sekadau in the 2020/2021 academic year. The data analysis technique applied was descriptive qualitative analysis based on the results of the research cycles. In the pre-cycle, the average score of inside-foot soccer dribbling was 62.64, outside-foot dribbling was 63.65, and instep dribbling was 63.57. In Cycle I, the average score of inside-foot dribbling increased to 72.45, outside-foot dribbling to 74.18, and instep dribbling to 71.98. In Cycle II, the average score of inside-foot dribbling increased further to 77.07, outside-foot dribbling to 77.15, and instep dribbling to 77.07.7.